(untitled) (Hekima Review, 2009)
An important goal of the development of African theologies and specifically African Christologies is the articulation of a religious, social and cultural worldview and conceptual framework which lends itself to the realization of that integrated identity which is truly African and truly Christian, and hence, African Christian identity. The fruit of genuine evangelization is the realization of a community of people reconciled to Christ, to one another and to the world. African theologies and specifically Christologies are important means of evangelization. African Christologies will achieve their goal of forging African Christian identity, i.e. an Africa reconciled to Christ, if it takes seriously the contemporary African context. This African context from which African Christian identity emerges can be understood from four integral perspectives: i) Very Religious Africa, ii) Africa, a Home to Rich Cultural Values, iii) Divided Africa and iv) Suffering Africa.